Model Data Envelopment Analysis untuk Mengukur Efisiensi Manajemen Satuan PAUD dalam Mendukung Capaian Numerasi Anak Usia Dini - Fera Luicia Tampi; Sumilat, Margareta Oktavia; Raflesia, Citra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to develop an output-oriented BCC-DEA mathematical model to measure the relative efficiency of early childhood education management in supporting children’s numeracy. A quantitative methodological study used deterministic simulation of 20 synthetic Decision Making Units (DMUs). Inputs comprised program expenditure per child, teacher ratio, media index, and stimulation hours; outputs comprised the numeracy index and the percentage of children meeting developmental criteria. The results identified seven efficient and 13 inefficient DMUs, with a mean pure technical efficiency of 0.9494. PAUD-09 appeared most frequently as a peer, followed by PAUD-17 and PAUD-18. Inefficient DMUs required output improvements of approximately 2.19%–20.72% with unchanged inputs, and sensitivity analysis showed very high correlations with the baseline model. BCC-DEA is therefore able to generate measurable efficiency, benchmarking, and improvement-target information; empirical use requires homogeneous DMUs, validated numeracy instruments, and data-quality audits. Keywords: BCC-DEA; Early Childhood Management; Early Numeracy; Educational Efficiency; Mathematical Modelling